Effect of Liraglutide on Cardiovascular Function and Myocardial Tissue Characteristics in Type 2 Diabetes Patients of South Asian Descent Living in the Netherlands: A Double‐Blind, Randomized, Placebo‐Controlled Trial. Issue 6 (4th December 2019) - Paiman, Elisabeth H.M.; van Eyk, Huub J.; van Aalst, Minke M.A.; Bizino, Maurice B.; van der Geest, Rob J.; Westenberg, Jos J.M.; Geelhoed‐Duijvestijn, Petronella H.; Kharagjitsingh, Aan V.; Rensen, Patrick C.N.; Smit, Johannes W.A.; Jazet, Ingrid M.; Lamb, Hildo J.
Abstract : Background: The glucagon‐like peptide‐1 (GLP‐1) receptor agonist liraglutide may be beneficial in the regression of diabetic cardiomyopathy. South Asian ethnic groups in particular are at risk of developing type 2 diabetes. Purpose: To assess the effects of liraglutide on left ventricular (LV) diastolic and systolic function in South Asian type 2 diabetes patients. Study Type: Prospective, double‐blind, randomized, placebo‐controlled trial. Population: Forty‐seven type 2 diabetes patients of South Asian ancestry living in the Netherlands, with or without ischemic heart disease, who were randomly assigned to 26‐week treatment with liraglutide (1.8 mg/day) or placebo. Field Strength/Sequence: 3T (balanced steady‐state free precession cine MRI, 2D and 4D velocity‐encoded MRI, 1 H‐MRS, T1 mapping). Assessment: Primary endpoints were changes in LV diastolic function (early deceleration peak [Edec], ratio of early and late peak filling rate [E/A], estimated LV filling pressure [E/Ea]) and LV systolic function (ejection fraction). Secondary endpoints were changes in aortic stiffness (aortic pulse wave velocity [PWV]), myocardial steatosis (myocardial triglyceride content), and diffuse fibrosis (extracellular volume [ECV]). Statistical Tests: Data were analyzed according to intention‐to‐treat. Between‐group differences were reported as mean (95% confidence interval [CI]) and were assessed using analysis of covariance (ANCOVA). Results: Liraglutide ( n = 22) compared with placebo ( n = 25) did not change Edec (+0.2 mL/s 2 × 10 ‐3 (–0.3;0.6)), E/A (–0.09 (–0.23;0.05)), E/Ea (+0.1 (–1.2;1.3)) and ejection fraction (0% (–3;2)), but decreased stroke volume (–9 mL (–14;–5)) and increased heart rate (+10 bpm (4;15)). Aortic PWV (+0.5 m/s (–0.6;1.6)), myocardial triglyceride content (+0.21% (–0.09;0.51)), and ECV (–0.2% (–1.4;1.0)) were unaltered. Data Conclusion: Liraglutide did not affect LV diastolic and systolic function, aortic stiffness, myocardial triglyceride content, or extracellular volume in Dutch South Asian type 2 diabetes patients with or without coronary artery disease. Level of Evidence: 1 Technical Efficacy Stage: 4 J. Magn. Reson. Imaging 2020;51:1679–1688.